Reaction rate in an evanescent random walkers system - Ré, Miguel A.; Bustos, Natalia C. (Instituto de Fisica de Liquidos y Sistemas Biologicos, 2015)
Diffusion mediated reaction models are particularly ubiquitous in the description of physical, chemical or biological processes. The random walk schema is an useful tool for formulating these models. Recently evanescent random walk models have received attention to include finite lifetime processes. For instance activated chemical reactions, such as laser photolysis, exhibit a different asymptotic limit when compared with immortal walker models. It is presented here a diffusion limited reaction model based on an one dimensional continuous time random walk on a lattice with evanescent walkers. The absorption probability density and the reaction rate are analytically calculated in the Laplace domain. A finite absorption rate is considered, a model usually referred to as imperfect trapping. Short and long time behaviors are analyzed.
Keywords: Random Walks; Diffusion Limited Reaction